2020
DOI: 10.1002/qj.3753
|View full text |Cite
|
Sign up to set email alerts
|

Summertime cloud phase strongly influences surface melting on the Larsen C ice shelf, Antarctica

Abstract: Surface melting on Antarctic Peninsula ice shelves can influence ice shelf mass balance, and consequently sea level rise. We show that summertime cloud phase on the Larsen C ice shelf on the Antarctic Peninsula strongly influences the amount of radiation received at the surface and can determine whether or not melting occurs. While previous work has separately evaluated cloud phase and the surface energy balance (SEB) during summertime over Larsen C, no previous studies have examined this relationship quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
63
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(76 citation statements)
references
References 63 publications
10
63
0
Order By: Relevance
“…3a, b). An overestimation of melt days was also found in other studies using AMPS and the polar WRF model over ice shelves (Grosvenor et al, 2014;King et al, 2008King et al, , 2015Kirchgaessner et al, 2019).…”
Section: Aws1 (%)supporting
confidence: 81%
See 2 more Smart Citations
“…3a, b). An overestimation of melt days was also found in other studies using AMPS and the polar WRF model over ice shelves (Grosvenor et al, 2014;King et al, 2008King et al, , 2015Kirchgaessner et al, 2019).…”
Section: Aws1 (%)supporting
confidence: 81%
“…During föhn conditions incoming shortwave radiation (SW↓) is hypothesised to be larger due to the clearance of clouds, which can occur in the lee of the AP mountains (Grosvenor et al, 2014;. However, due to the large annual cycle in SW↓ in the polar regions, the seasonal magnitude of SW↓ could bias the difference between föhn and non-föhn days if they are not evenly distributed throughout the year.…”
Section: Annually Averaged Impact Of Föhnmentioning
confidence: 99%
See 1 more Smart Citation
“…The poor representation of clouds in many regional climate models causes issues in the accuracy of SEB and melt information. Recently, Gilbert et al (2020) found that cloud-phase during the austral summer strongly influences the amount of melting on the LCIS and can determine whether melting is simulated or not by the MetUM model.…”
Section: Discussionmentioning
confidence: 99%
“…The 360 conclusions may not hold for winter clouds in the region, which contain less supercooled liquid water (Listowski et al, 2019) and are less prone to riming, and thus may not favour BR. Nevertheless, summer clouds play a critical role in the surface melting of the ice-shelf in the vicinity of Weddell Sea (Gilbert et al, 2020) in West Antarctica and thus their accurate microphysical representation in models is of great importance. 365…”
Section: Conclusion 355mentioning
confidence: 99%